SiC Nanowires Bridged Graphene Aerogels with a Vertically Aligned Structure for Highly Thermal Conductive Epoxy Resin Composites and Their Mechanism - Zhao, Xintong; Wu, Wei; Drummer, Dietmar; Wang, Yi; Cui, Sufei; Liu, Chao; Lu, Zijian; Li, Shuo; Chen, Qiming (ACS Applied Electronic Materials, 2023)
Thermal conductive composites have a wide application in the electronic packaging field, and fabricating three-dimensional (3D) graphene aerogels by the self-assembly method is a facile way to construct thermal conductive networks in polymer composites. But those self-assembled graphene aerogels can only endow composites with a limited thermal conductivity because (1) abundant defects on RGO sheets reduce their intrinsic thermal conductivity and (2) massive edges and gaps in aerogels cause severe phonon scattering. Many works before have been done to heal the defects by high-temperature annealing, but the works of filling gaps and decreasing phonon scattering are rare. Herein, we designed a facile route to synthesize SiC nanowires on the edges of RGO sheets for connecting adjacent RGO sheets, decreasing phonon scattering, and enhancing thermal conduction efficiency in graphene aerogels. Before that, RGO/Si aerogels with vertically aligned structures were obtained by the chemical reduction method and the freeze-drying method to enhance their through-plane thermal conduction efficiency. When the initial mass ratio of GO solute/silicon powder was 5:1, HGA-5 endowed the EP composite with a high through-plane thermal conductivity of 3.59 W m-1 K-1 at a relatively low filler loading of 2.87 wt %. Finite element analysis was applied to illustrate the thermal conductive mechanism of the hybrid aerogels-filled EP composites. The EMI shielding performance of the composites was also discussed in this work.
CRIS-Team WoS Importer:2023-06-02